2015
DOI: 10.4103/0301-5742.171317
|View full text |Cite
|
Sign up to set email alerts
|

A new dimension to cephalometry: DW plane

Abstract: Numerous cephalometric norms or standards have been given in past for various population in terms of age and ethinic origin. An accurate sagittal jaw relationship is critically important in orthodontic diagnosis and treatment planning. Various angular and linear measurements have been proposed that can be inaccurate because they depend on various factors. [1,2] For example Wits appraisal, ANB angle and nasion perpendicular are currently used by practitioners to diagnose the sagittal jaw relationship but all of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The present study showed it to be accurate and reliable in diagnosing skeletal class I cases compared to class II and III cases, where it was least reliable, against the previous results (Gul et al, 2018). DW linear (Hatewar et al, 2015) measurement involves anterior cranial base tracing and a diagnostic quality cephalometric image is essential. The current study showed it to be less accurate and reliable in diagnosing skeletal discrepancy as compared to other linear parameters taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed it to be accurate and reliable in diagnosing skeletal class I cases compared to class II and III cases, where it was least reliable, against the previous results (Gul et al, 2018). DW linear (Hatewar et al, 2015) measurement involves anterior cranial base tracing and a diagnostic quality cephalometric image is essential. The current study showed it to be less accurate and reliable in diagnosing skeletal discrepancy as compared to other linear parameters taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…DW linear (Hatewar et al, 2015) measurement involves anterior cranial base tracing and a diagnostic quality cephalometric image is essential. The current study showed it to be less accurate and reliable in diagnosing skeletal discrepancy as compared to other linear parameters taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It is also found that (T-w) line is reliable method for examining overall changes (M. Arat et al, 2001;Z. M. Arat et al, 2010;Hatewar et al, 2015).…”
Section: Cephalometric Analysismentioning
confidence: 92%
“…the growth of middle cranial base is completed in early periods and at the age of 7 years, maintaining its stability in all developmental phases (Björk and Skieller, 1983). Two cephalometric points located in the middle cranial base showed high stability over years (Björk and Skieller, 1983;Hatewar et al, 2015). The points are known to be as the following: the intersection point of the lower contours of the anterior clinoid processes and the contour of the anterior wall of the sella, also called as Walker's point (T, W), and the intersection point of the middle cranial fossa by the greater wing of the sphenoid bone, also called as Wing point (w) (Arat et al, 2010;Björk and Skieller, 1983).…”
Section: Cephalometric Analysismentioning
confidence: 95%
“…Examples of such measurements include: YEN angle formed by the points S, M, G defining the sagittal relationship between the maxilla and the mandible, first described by Neel et al in 2009 [ 10 ]. Pi analysis referring to the angular measurement Pi (GG`M) and the linear measurement Pi (G`M`) based on the points G, M from which the perpendicular goes to the true horizontal plane in the natural position of the head, defining the sagittal relationship between the maxilla and the mandible [ 11 ], first described by Kumar et al in 2012 [ 12 ] W angle formed by the points S, M, G, defining the sagittal relationship between the maxilla and mandible, first described by Bhad et al in 2011 [ 13 ] SAR angle formed by the points M, G, W, defining the sagittal jaw base discrepancy, described by Sonahita et al in 2015 [ 14 ] DW angle using Walker and Wing (WW) points to assess the sagittal discrepancy, described by Hatewar et al in 2015 [ 15 ] Tau angle formed by the points T, M, G, defining the sagittal relationship between the maxilla and the mandible, first described by Gupta et al in 2020 [ 6 ] R angle formed by the points N, C, Me to assess the vertical discrepancy, first described by Rizwan and Mascarenhas in 2013 [ 16 ] KP (extraoral) plane and points NS, SAE bilaterally to assess the vertical discrepancy, first described by Kattan et al in 2018 [ 17 ] Superior border of the zygomatic arch to assess the vertical discrepancy as an alternative to the Frankfurt horizontal line introduced by Park et al in 2019 [ 18 ] …”
Section: Introductionmentioning
confidence: 99%